Narracja polityczna republikanów w kształtowaniu kampanii wyborczej w wyborach prezydenckich w USA w 2024 r. - Pankiewicz, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Republican Party, along with the Democratic Party, occupies a key position in the US party system. Since the party was founded in 1854, the political discourse has changed. Republicans during the Civil War advocated the abolition of slavery. However, in the 1960s and 1970s, the party`s political narrative lobbied for not abolishing racial divisions in the southern states. This article, illustrated the history of the Republican Party, its main tenets, the figure of its candidate from the 2024 election campaign, and the impact of the party`s political narrative on the 2024 presidential campaign.
Keywords: Trump, Donald John (prezydent Stanów Zjednoczonych; 1946- ); wybory; populism; Republikanie; GOP; elections; populizm; Republicans